THE INFLUENCE OF WORK ENVIRONMENT AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE AT UPT OFFICE. SAMSAT BULUKUMBA - Adelia, Haera; Nurman; Idris, Abdi Akbar; Musa, Chalid Imran; Haeruddin, M. Ikhwan Maulana (Transpublika Publisher, 2023)
This study aimed to examine the impact of work environment and work motivation on employee performance at the UPT office, Samsat Bulukumba. The sample population comprised 28 employees from the UPT office, and a saturated sampling method was employed for this quantitative research. Primary and secondary data were collected using a questionnaire distribution technique. The data were analyzed using SPSS 21. The findings indicated a positive relationship between the work environment (X1) and employee performance (Y), with a coefficient value of 0.396 (>2.059) and a significant value of 0.005 (<0.05). However, the work motivation (X2) exhibited a negative effect on employee performance (Y), with a coefficient value of -0.070 (<2.059) and a non-significant value of 0.559 (>0.05). The coefficient of determination revealed that the variables of work environment and work motivation accounted for 29.9% of the influence on employee performance, while the remaining percentage was attributed to other variables beyond the scope of this study.